Estado Capitalista brasileiro: análise dos direitos sociais em tempos de ortodoxia neoliberal - Mustafa, Patrícia Soraya (Programa de Pós-Graduação em Serviço Social e Curso de Graduação em Serviço Social da Universidade Federal de Santa Catarina, 2019)
Abstract This article is based on theoretical and documentary research and aims to analyze the document Uma Ponte para o Futuro [A bridge to the future], as well as the measures carried out by the (illegitimate) Brazilian government headed by the Brazilian Democratic Movement (MDB) in the period 2016-2018. Among the measures analyzed are the labor counterreform, the Constitutional Amendments (EC) 93 and 95, and the bill proposing a social security counterreform. The article emphasizes the impact of such measures on the working class. The study is based on the understanding of the capitalist state as ontologically subordinated to the interests of capital, which is expressed in the characteristics of the policies adopted and proposed by the MDB’s government in Brazil. When analyzing the scope of the economic and social policy of the period, the article makes clear who is penalized with the measures put forward by the government.

Resumo Este artigo, respaldado em uma pesquisa teórica e documental, tem o intuito de analisar o documento Uma Ponte para o Futuro, e para além dele, os feitos colocados em curso pelo atual governo (ilegítimo) do Movimento Democrático Brasileiro (MDB), como a contrarreforma trabalhista, as Emendas Constitucionais (EC) nº 93 e 95 e a proposta de contrarreforma da previdência social; elucidando seus impactos para a classe trabalhadora. Para realizar este estudo, partimos da compreensão de que o Estado capitalista está ontologicamente subordinado aos interesses do capital, e hoje, isso se expressa nas medidas adotadas e propostas pelo atual governo. Evidenciamos, ao final, após analisarmos o escopo da política econômica e social atual, quem vem sendo penalizado com essas medidas na sociedade brasileira.
The Brazilian capitalist state: Analysis of social rights in times of neoliberal orthodoxy
Keywords: Capitalist state; Neoliberalism; Uma Ponte para o Futuro; Fiscal adjustment; Social rights; Estado capitalista; Neoliberalismo; Uma Ponte para o Futuro; Ajuste fiscal; Direitos sociais